Moderate knowledge is not enough – a longitudinal study on knowledge and acceptance of evolution among pre-service science teachers - Judith Lanka; Pitt Hild; Anna Beniermann (Zeitschrift für Didaktik der Biologie - Biologie Lehren und Lernen)
Understanding evolution is crucial for comprehending biology and addressing contemporary biological crises. To teach evolution effectively, science teachers need profound content knowledge of evolution and a high acceptance of evolution. On average, across Europe, science teachers’ knowledge of evolution is only low to moderate, while their acceptance levels vary. Switzerland has recently integrated fundamental concepts of evolution into school curricula, from early childhood education to secondary school. However, there is limited information on pre-service science teachers’ knowledge and acceptance of evolution and the effectiveness of biology courses within teacher education programs in Switzerland. In a longitudinal (n = 32) and cross-sectional (n = 658) study spanning 3 years, the knowledge and acceptance of evolution among pre-service science and non-science teachers in Switzerland were surveyed using two established questionnaires (KAEVO 2.0 and ATEVO). The knowledge of evolution observed in pre-service science teachers increased throughout their studies. However, even upon completion of their studies, knowledge remained at a moderate level. The students still held persistent alternative conceptions, e.g. regarding the heredity of phenotype changes, variation, and fitness. The comparison group, without biology courses, exhibited low levels of knowledge at all measurement points. Both groups, however, demonstrated high levels of acceptance. The Model of Educational Reconstruction is discussed as an approach for teacher education to improve the effectiveness of teaching evolution, along with a stronger focus on professional orientation. Specifically, imparting school-relevant knowledge, considering students’ alternative conceptions, and the repeated application of core concepts could contribute to increasing student learning outcomes.